Unhealthy Profits - Christopher Mouré; Shai Gorsky (Promoting Economic Pluralism, 2023)
FROM THE ARTICLE: At the end of November 2023, the New York Times published an editorial: Why Are Nonprofit Hospitals Focused More on Dollars Than Patients? It is certainly a valid question. Most people might assume that not-for-profit (NFP) organisations focus on providing a public benefit rather than profit. At most, common wisdom suggests that any income derived from providing a service should be reinvested into expanding or improving the service. There is no obvious reason why a NFP should accumulate large profits over years. Yet in the NFP world of large US hospitals, profit, rather than public purpose, seems to have become the guiding light.
Keywords: P; P1; L3; L33; I1; I11; 330; differential accumulation; hospitals; not-for-profit; profit; United States